Análise compreensiva do significado do atendimento ao adolescente realizado pelos profissionais de saúde da atenção primária do município de Viçosa-MG - Bruno David Henriques (2009)
This work is a study of qualitative nature, with phenomenological approach, which had as objective to understand the meaning of assistance to adolescents conducted by primary care professionals in the municipality of Viçosa-MG. The research was realized with graduatedprofessionals, doctors and nurses, working in teams of the Family Health Strategy. Data were collected in February and March 2009, through an open individual interview with professionals who accepted to participate in the study. It was an open interview, conducted by a guiding question: "What does it mean for you to assist the teenager in primary care? " Bythe criterion of repetition of words, it was possible to get to twelve interviewees, whose speeches were evaluated according to ideographic analysis proposed by Martins and Bicudo (1989), which allowed us to build twelve thematic units. These units converged to three largecategories of analysis that clarify the care to adolescents: "Assistance to adolescents: the challenges of primary care", "Assistance to adolescents in primary care: characteristics of the practice care", "Answering the adolescent: a need of primary care". For the professionals whoparticipated in the search, the assistance to adolescents is still a major challenge, which has many obstacles. In this context there are issues related to the difficulty in dealing with this population, the lack of training, the overload of work, among other elements. Other points thatwere highlighted are related to the work developed by the professionals in teams, often directed to the characteristics, risks and problems of adolescence. Participants also say that it is necessary to assist the adolescent and the health service should be organized to perform thisjob. The identification of the phenomenon indicates that we have important issues to discuss and improve, related to attendance in primary care to adolescents. This context various elements should be involved, among them are the professional and the adolescent, which arethe key components of this organization.